INTANGIBLE ASSET DALAM PENGEMBANGAN BISNIS PERSPEKTIF MAQASID SYARIAH - Khusnudin Khusnudin (Journal of Islamic Economy and Business (JIsEB), 2020)
Introduction: The purpose of this study is to find out how to manage intangible assets from the perspective of maqasid sharia.. Background Problems: Developing business in the 4.0 era need competence in order to obtain the expected to get benefits. Various types of capital (tangible assets) are allocated in order to win the competition on a global scale. Several countries have given more attention to intangible assets. The perfecness of Islam in explaining intangible assets is important to be understood in order to determine the priority types of capital to develop business in the 4.0 era. Research Methods: This qualitative research uses a literature study approach and Islamic maqasid angle as its analysis. Results: Intangible assets are related to reason work and human resources, on a priority scale than precedence over material assets (tangible assets). Intangible asset management according to Islamic normative rules will provide material benefits (tangible) and non-material (intangible) to obtain happiness in the world and the here after. Conclusion:. Intangible assets dominate the aspects of maintaining reason and human resources such as faith, honesty, trustworthiness, professionalism, justice, responsibility, and courage.